Neospora caninum truncated recombinant proteins formulated with liposomes and CpG-ODNs triggered a humoral immune response in cattle after immunisation and challenge - Novoa, María Belén (2021)
Abortions caused by Neospora caninum are a serious problem in cattle production and require effective immunoprophylaxis. The objective of this work was to assess the humoral immune response to four recombinant (r) N. caninum antigens in cattle after immunisation and challenge. MIC1 and MIC3 proteins from the micronemes, SRS2 from the surface of tachyzoites, and GRA7 from the dense granules were expressed as truncated recombinant proteins in Escherichia coli. Cationic liposomes (Lip) and CpG oligodeoxynucleotides (CpG-ODNs) were used as adjuvant. Steers were assigned to three groups of six steers each and were inoculated twice subcutaneously, 21 days apart. The rP + Lip + CpG-ODN group received the truncated recombinant proteins rMIC1, rMIC3, rSRS2 and rGRA7 formulated with the adjuvant; the Lip + CpG-ODN group received the adjuvant alone; and the PBS group received sterile phosphate-buffered saline. All steers were subcutaneously challenged with the NC-1 strain of N. caninum 35 days after the second dose of immunisation. Steers from the rP + Lip + CpG-ODN group developed specific IgG, IgG1 and IgG2 against the four recombinant proteins after immunisation. After challenge, IgG against rMIC1 and rMIC3 was detected in rP + Lip + CpG-ODN group and against rSRS2 and rGRA7 in all groups. IgG1 and IgG2 against the four recombinant proteins remained high after challenge in the rP + Lip + CpG-ODN group. Indirect ELISA detected anti-N. caninum antibodies after challenge in all groups, with the highest level of antibodies being detected in the rP + Lip + CpG-ODN group. The recombinant vaccine formulated with rMIC1, rMIC3, rSRS2 and rGRA7 using Lip + CpG-ODN as adjuvant was immunogenic in cattle and the humoral immune response after challenge was enhanced in vaccinated cattle.